A biochemical study of some of the hydrolases to be found in the latex of the pawpaw, Carica papaya L - Skelton, Gerald S (Division of Chemical Pathology, 2020)
Using fresh papaya latex as the starting material, this thesis describes methods for the isolation and purification of three major proteinases by column adsorption chromatography; a comparative study of certain salient chemical and physical properties of these enzymes is presented. Reference is made to some conflicting results in the literature concerning papain studies, and an effort has been made in this work, by further experimentation, to account for some of the discrepancies. A supplementary study of biochemical interest has been the collecting of latex from the same growing fruit at fixed time intervals : analysis of the samples shows the changes in the yields of latex and enzyme content during the six months that the fruit takes to ripen.